(untitled) (Fiep Bulletin - online, 2013)
The aim of this study were to characterize the behavior of self-care presented by the patients submitted to the bariatric surgery among the years of 2000 and 2007, in the University Hospital of Maringá (UHM). A descriptive cross sectional study was accomplished. Of the 109 patients submitted the procedure, were located 30 patient, which answered to phone inquiry. The statistical analysis involved measures of central tendency, and when pertinent statistics descriptive were used, beyond accomplishment of non parametric tests and parametric for dependent and independent samples. The bariatric surgery promoted a significant weight reduction from 114,5 (±15,5) to 74,1 (±8,6) with p <0,001. BMI were also significantly reduced 42,3 (±9,9) to 27,2 (±6,2) p <0,001. In relation to the self-care 90% of the patients accomplish exams and filed them, on the other hand only 30% indicated to pratice physical activity regularly. The use of medicines were around 50% and only 20% don’t make use of dietary supplements. It can be concluded that the bariatric surgery is very effective in the weight and BMI reduction. However, the attendance of the multidisciplinary team in the postoperative period needs to be more effective.